Socio economic challenges and coping strategies against COVID-19 among dentists of Nepal - Agrawal Sagtani, Reshu; Adhikari, Pravindra; Dixit, Siddharth; Basnet Dixit, Punam; Sagtani, Alok (Journal of Patan Academy of Health Sciences, 2022)
Introduction: COVID-19 has posed various challenges to health care professionals including dentists. We aimed to study financial impact, socio- economic challenges, coping strategies and areas where dentists of Nepal require support during the current pandemic. Method: A descriptive study was conducted among registered dentists who were currently involved in clinical practice in Nepal. Data was collected via semi-structured online google form during the period of August – October 2020 through non-probability sampling. The online responses from google forms were transformed to datasheets which were analyzed using Microsoft Excel and summarized using descriptive statistics. Result: More than a quarter (127, 29.8%) of the dentists were not able to practice dentistry during the pandemic. Among the salaried dentists, 113 (34.2%) of them did not receive any salary and 67 (15.7%) lost their jobs. More than 50% percent of decline in monthly income was experienced by 80 (18.7%). The most common challenge faced by the dentists was reduced income (95.2%) followed by access to PPE and sanitizers (72.9%). Social distancing was the most common (87.2%) coping strategy followed by strict use of PPE (86.9%), acquiring correct information regarding prevention of COVID-19 (76.8%). Provision of PPE was the area where 147 dentists needed the most support (36.4%) followed by cash allowance (31.7%) and rent waiver (28.4%). Conclusion: The study showed that dentists in Nepal are facing serious financial challenges due to the current pandemic. The current study highlights a need to create a support system for dentists to sustain their clinical practice during the pandemic.